2020
DOI: 10.1140/epjc/s10052-020-08772-4
|View full text |Cite
|
Sign up to set email alerts
|

Schwarzschild-like solutions in Finsler–Randers gravity

Abstract: In this work, we extend for the first time the spherically symmetric Schwarzschild and Schwarzschild–De Sitter solutions with a Finsler–Randers-type perturbation which is generated by a covector $$A_\gamma $$ A γ . This gives a locally anisotropic character to the metric and induces a deviation from the Riemannian models of gravity. A natural framework for this study is the Lorentz tangent bundle of a spacetime manifo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…The solution of these equations for this metric is presented at the end of the section. An extended study of this model can be found in [40,44].…”
Section: Basic Structure Of the Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…The solution of these equations for this metric is presented at the end of the section. An extended study of this model can be found in [40,44].…”
Section: Basic Structure Of the Modelmentioning
confidence: 99%
“…In this work, we will follow the model presented in [40]. The metric g μν is the classic Schwarzschild one:…”
Section: Basic Structure Of the Modelmentioning
confidence: 99%
See 3 more Smart Citations